Therapeutic efficacy and safety of Xuebijing in traumatic brain injury: systematic review and meta-analysis - Sun, Yihan; Li, Jiaqi; Cui, Xinyue; Yu, Meiyu; Xiao, Boying; Lv, Junyuan; Li, Ziqi; Wei, Zhijing; He, Niaoyao; Li, Zhuoyu; Wen, Hao (Frontiers in Pharmacology, 2025)
BackgroundTraumatic brain injury (TBI) represents a major global health challenge. Several clinical studies have suggested that Xuebijing (XBJ)—a patented Chinese botanical drug preparation may confer neuroprotective and anti-inflammatory benefits in TBI. This systematic review and meta-analysis aimed to evaluate the therapeutic efficacy and safety of XBJ as an adjunctive treatment for TBI.Materials and methodsA comprehensive search was performed across nine English and Chinese databases for randomized controlled trials (RCTs) evaluating XBJ in TBI patients, with records screened up to February 2025. Two independent reviewers conducted study selection and data extraction. Pooled estimates were calculated using fixed- or random-effects models, expressed as standardized mean differences (SMDs) or risk ratios (RRs) with 95% confidence intervals (CIs). Trial sequential analysis (TSA) and the GRADE framework were used to assess evidence robustness and certainty. Subgroup and sensitivity analyses explored potential dose–response patterns and sources of heterogeneity.ResultsA total of 33 RCTs involving 3,215 patients with TBI met the inclusion criteria. Pooled analysis demonstrated that XBJ significantly improved neurological function, yielding higher Glasgow Coma Scale (GCS) scores (SMD = 0.66, 95% CI 0.51–0.80) and Glasgow Outcome Scale (GOS) scores (SMD = 0.78, 95% CI 0.39–1.16), while reducing all-cause mortality (RR = 0.56, 95% CI 0.44–0.69). XBJ also markedly decreased systemic inflammatory biomarkers, including C-reactive protein (CRP; SMD = −1.34), tumour necrosis factor-alpha (TNF-α; SMD = −0.98), and interleukin-6 (IL-6; SMD = −0.98) (all p < 0.01). No significant increase in adverse drug events (ADEs) was observed (RR = 1.32, 95% CI 0.58–2.96). Subgroup analyses indicated a dose-dependent relationship, with cumulative doses >1,400 mL and twice-daily intravenous administration associated with greater neurological and anti-inflammatory benefits.ConclusionXBJ appears to be an effective and safe adjunctive therapy for TBI, improving neurological outcomes and reducing inflammatory responses. Dose-dependent effects support the optimization of treatment protocols.